(untitled) (Docentes 2.0 Journal, 2024)
Acquiring a second language, especially in school contexts, faces challenges beyond memorizing vocabulary and grammatical structures. The objective of the research was to apply theater as a pedagogical tool in the English classroom through lesson plans that integrate theater exercises designed to improve oral comprehension and production. It was carried out using the inductive-deductive method, a pragmatic paradigm, mixed approach, sequential type, sequential exploratory design, and cross-sectional. Diagnostic surveys were applied to evaluate the confidence and prior knowledge of 13 fourth-grade students from the Colegio La Presentación de Tunja, who participated in theater workshops designed as structured lesson plans. The workshops integrated theater components to enrich the learning environment and facilitate the acquisition of communicative skills in English. The research collected data through class diaries, observation grids, and final surveys, analyzing the workshops’ effectiveness in students’ learning, attitudes, and confidence in using English as a second language. This approach provided an in-depth understanding of the influence of theatre as a pedagogical tool in the context of the L2 classroom at the school above.